Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10681-008-9810-6
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific QTLs and their different epistatic interactions for pod dehiscence in soybean [Glycine max (L.) Merr.]

Abstract: Pod dehiscence (PD) prior to harvest results in serious yield loss in soybean. Two linkage maps with simple sequence repeat (SSR) markers were independently constructed using recombinant inbred lines (RILs) developed from Keunolkong (pod-dehiscent) £ Sinpaldalkong (pod-indehiscent) and Keunolkong £ Iksan 10 (pod-indehiscent). These soybean RIL populations were used to identify quantitative trait loci (QTLs) conditioning resistance to PD. While a single major QTL on linkage group (LG) J explained 46% of phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
4
42
0
2
Order By: Relevance
“…In contrast to results obtained from interspecific genetic analysis, a major QTL for pod dehiscence has been identified in the cultivated species on chromosome 16 (14)(15)(16)(17). An anatomical analysis using near-isogenic lines (NILs) for this QTL, designated as qPDH1, has revealed no marked differences in suture morphology, including that of secondary cell-wall formation (18) (Fig.…”
mentioning
confidence: 76%
“…In contrast to results obtained from interspecific genetic analysis, a major QTL for pod dehiscence has been identified in the cultivated species on chromosome 16 (14)(15)(16)(17). An anatomical analysis using near-isogenic lines (NILs) for this QTL, designated as qPDH1, has revealed no marked differences in suture morphology, including that of secondary cell-wall formation (18) (Fig.…”
mentioning
confidence: 76%
“…This consensus sequence spanned 915. 4 Mb, representing a coverage of 97.65% of the G. max published genome sequence and an average mapping depth of 43-fold. The nucleotide sequence of the G. soja genome, which contains 2.5 Mb of substituted bases and 406 kb of small insertions/deletions relative to G. max, is ∼0.31% different from that of G. max.…”
mentioning
confidence: 99%
“…Out of these 46 plants with 237 bp marker all but one plant had pod shattering more than 25%. Kang et al 2009), had reported that Satt166 had a minor QTL for pod dehiscence on Linkage group L. Satt166 marker was originally described by Cregan et al (1999) to be present on soybean linkage group 'L'. Kang et al, (2009) reported that Satt166 amplified marker for a minor pod dehiscence QTL that had LOD score of 3.7.…”
Section: Validation Of Markers For Pod Shattering Resistancementioning
confidence: 99%
“…Yamada et al, (2009) reported that shattering-resistant cultivars harbor recessive shattering-resistance allele at qPDH1 regardless of their origin and that molecular markers near qPDH1 could be used for markerassisted selection for shattering resistance in soybean. Kang et al (2009) reported four minor QTLs for pod dehiscence in addition to a qPDH1 which explained 46% of phenotypic variation. Suzuki et al (2010) carried out high-resolution mapping of qPDH1 to a 134-kb region on chromosome 16 (formerly linkage group J) to develop useful selection markers.…”
Section: Introductionmentioning
confidence: 99%